Object Case Marking: English Influence on the Use of Estonian by Three Estonian-English Bilingual Children - Torn, Reeli (Kalbotyra, 2003)
The present paper reports the results of one part of a study conducted on the native language of three Estonian-English bilingual children living in Britain. This part focuses on object case marking. The study found that the native language of these children demonstrated English influence in their systematic overuse of the partitive to mark direct objects in Estonian. The plausibility of regarding this as a transfer effect is supported by two considerations. First, the children have limited exposure to Estonian speakers in England, so that English has become their dominant language. Second, the children’s simplification of object marking patterns conforms to the much simpler English pattern. The primary subjects were asked to translate 40 English sentences (with 43 object contexts) into Estonian. A set of Estonian control subjects were given a completion task with the same sentences in Estonian. The results of the study revealed that the primary subjects overwhelmingly used the partitive in marking direct objects, even in contexts where either the genitive or nominative marking was required. The control subjects demonstrated a consistent use of the three object cases in appropriate contexts.